Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1521/suli.2008.38.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Building Models for the Relationship Between Attitudes Toward Suicide and Suicidal Behavior: Based on Data from General Population Surveys in Sweden, Norway, and Russia

Abstract: Our aim was to build a model delineating the relationship between attitudes toward suicide and suicidal behavior and to assess equivalence by applying the model on data from different countries. Representative samples from the general population were approached in Sweden, Norway, and Russia with the Attitudes Toward Suicide (ATTS) questionnaire. Data on experience of suicidal behavior among significant others and self-reported suicidal expressions were also collected. Structural equation modeling resulted in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages. Suicide rates in China, like in most other countries, increase with age (Phillips et al, 2002) so the decreasing acceptability of suicide with age does not appear to substantially reduce the rates of suicidal behavior.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages. Suicide rates in China, like in most other countries, increase with age (Phillips et al, 2002) so the decreasing acceptability of suicide with age does not appear to substantially reduce the rates of suicidal behavior.…”
Section: Discussionmentioning
confidence: 60%
“…Prior research has not compared attitudes in different population groups and very few studies employ multivariate analysis to assess the factors independently related to attitudes about suicide (Salander Renberg et al, 2008; Seidlitz et al, 1995), so it is only possible to compare some of our results with prior studies. Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations